NEW DEVELOPMENTS REGARDING THE ADMISSIBILITY CRITERIA OF INDIVIDUAL APPLICATIONS TO THE EUROPEAN COURT OF HUMAN RIGHTS - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
This paper deals with certain admissibility criteria of an individual application before the European Court of Human Rights. This is one of the most important issues in the Court’s practice and it represents a necessary condition for deciding on the merits of submitted applications. The period of six months for submitting the application is introduced in order to preserve legal certainty but also it serves for the interests of states because it prevents that final domestic decisions are questioned indefinitely. The Court can declare each application inadmissible if it considers that the applicant has not suffered a significant disadvantage, unless respect for human rights as defined in the Convention and the Protocols requires an examination of the application. Also, the application cannot be rejected on this ground if the case has not been duly considered by a domestic tribunal. Protocol No. 15 to the Convention, which has not yet entered into force, envisages the deletion of this last possibility and also reducing the period for submitting the application from six to four months.